Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
\(\left(\frac{3}{9}.x-5\right)^2=\frac{9}{49}\)
\(\Rightarrow\orbr{\begin{cases}\frac{3}{9}x-5=\frac{3}{7}\\\frac{3}{9}x-5=-\frac{3}{7}\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}\frac{3}{9}x=\frac{3}{7}+5\\\frac{3}{9}x=-\frac{3}{7}+5\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}\frac{3}{9}x=\frac{38}{7}\\\frac{3}{9}x=\frac{32}{7}\end{cases}}\)
\(\Rightarrow\orbr{\begin{cases}x=\frac{114}{7}\\x=\frac{96}{7}\end{cases}}\)
Vậy \(\orbr{\begin{cases}x=\frac{114}{7}\\x=\frac{96}{7}\end{cases}}\)
Chúc bạn học tốt !!!!
a: \(\Leftrightarrow3x+9=-2x+6\)
=>5x=-3
hay x=-3/5
b: =>3/x=y/35=3/7
=>x=7; y=15
c: =>9x/5=-3/5
=>9x=-3
hay x=-1/3
d: =>x+2/26=-1/4
=>x+2=-13/2
hay x=-17/2
2840 + [ ( 999 - 9 x X ) : 60 ] x 24 = 3200
=> [ ( 999 - 9 x X ) : 60 ] x 24 = 3200 - 2840 = 360
=> ( 999 - 9 x X ) : 60 = 360 : 24 = 15
= > 999 - 9 x X = 15 x 60 = 900
= > 9 x X = 999 - 900 = 99
=> X = 99 : 9 = 11
Đúng NHa !!!
2840+[(999-9.x):60].24=3200
[(999-9.x):60].24 = 3200 - 2840
[(999-9.x):60].24 = 360
(999-9.x):60 = 360 : 24
(999-9.x):60 = 15
999-9.x = 15 . 60
999-9.x = 900
9.x = 999 - 900
9.x = 99
x = 99 : 9
x = 11
Vậy x=1
a: =>x-2/5=3/4:1/3=3/4*3=9/4
=>x=9/4+2/5=45/20+8/20=53/20
b: =>x-2/3=7/3:4/5=7/3*5/4=35/12
=>x=35/12+2/3=43/12
c: 1/3(x-2/5)=4/5
=>x-2/5=4/5*3=12/5
=>x=12/5+2/5=14/5
d: =>2/3x-1/3-1/4x+1/10=7/3
=>5/12x-7/30=7/3
=>5/12x=7/3+7/30=77/30
=>x=77/30:5/12=154/25
e: \(\Leftrightarrow x\cdot\dfrac{3}{7}-\dfrac{2}{7}+\dfrac{1}{2}-\dfrac{5}{4}x+\dfrac{5}{2}=0\)
=>\(x\cdot\dfrac{-23}{28}=\dfrac{2}{7}-3=\dfrac{-19}{7}\)
=>x=19/7:23/28=76/23
f: =>1/2x-3/2+1/3x-4/3+1/4x-5/4=1/5
=>13/12x=1/5+3/2+4/3+5/4=257/60
=>x=257/65
i: =>x^2-2/5x-x^2-2x+11/4=4/3
=>-12/5x=4/3-11/4=-17/12
=>x=17/12:12/5=85/144
a) \(12\dfrac{1}{3}-\left(3\dfrac{3}{4}+4\dfrac{3}{4}\right)=\dfrac{37}{3}-\left(\dfrac{15}{4}+\dfrac{19}{4}\right)\)
\(=\dfrac{37}{3}-\dfrac{34}{4}=\dfrac{37}{3}-\dfrac{17}{2}=\dfrac{74}{6}-\dfrac{51}{6}=\dfrac{23}{6}\)
b) \(3\dfrac{5}{6}+2\dfrac{1}{6}.6=\dfrac{23}{6}+\dfrac{13}{6}.6=\dfrac{23}{6}+\dfrac{78}{6}=\dfrac{101}{6}\)
c) \(3\dfrac{1}{2}+4\dfrac{5}{7}-5\dfrac{5}{14}=\dfrac{7}{2}+\dfrac{33}{7}-\dfrac{75}{14}=\dfrac{49}{14}+\dfrac{66}{14}-\dfrac{75}{14}=-\dfrac{92}{14}=-\dfrac{46}{7}\)
d) \(4\dfrac{1}{2}+\dfrac{1}{2}:5\dfrac{1}{2}=\dfrac{9}{2}+\dfrac{1}{2}:\dfrac{11}{2}=\dfrac{9}{2}+\dfrac{1}{2}.\dfrac{2}{11}=\dfrac{9}{2}+\dfrac{1}{11}=\dfrac{99}{22}+\dfrac{2}{22}=\dfrac{101}{22}\)
a. \(12\dfrac{1}{3}-\left(3\dfrac{3}{4}+4\dfrac{3}{4}\right)=\dfrac{37}{3}-\left(\dfrac{15}{4}+\dfrac{19}{4}\right)\)
\(=\dfrac{37}{3}-\dfrac{34}{4}=\dfrac{23}{6}\)
\(b.3\dfrac{5}{6}+2\dfrac{1}{6}.6=\dfrac{23}{6}+13=\dfrac{101}{6}\)
\(c.3\dfrac{1}{2}+4\dfrac{5}{7}-5\dfrac{5}{14}=\dfrac{7}{2}+\dfrac{33}{7}-\dfrac{75}{14}=\dfrac{20}{7}\)
d \(4\dfrac{1}{2}+\dfrac{1}{2}:5\dfrac{1}{2}\)
\(=\dfrac{9}{2}+\dfrac{1}{2}:\dfrac{11}{2}\)
\(=\dfrac{9}{2}+\dfrac{1}{11}\)
\(=\dfrac{101}{22}\)
a: \(\Leftrightarrow\left(\dfrac{13}{4}:x\right)\cdot\left(-\dfrac{5}{4}\right)=\dfrac{-10}{6}-\dfrac{5}{6}=\dfrac{-15}{6}=\dfrac{-5}{2}\)
\(\Leftrightarrow\dfrac{13}{4}:x=\dfrac{5}{2}\cdot\dfrac{5}{4}=\dfrac{25}{8}\)
hay \(x=\dfrac{13}{4}:\dfrac{25}{8}=\dfrac{13}{4}\cdot\dfrac{8}{25}=\dfrac{26}{25}\)
b: \(\Leftrightarrow\dfrac{3}{4}:x=\dfrac{11}{36}-\dfrac{1}{4}=\dfrac{2}{36}=\dfrac{1}{18}\)
=>\(x=\dfrac{3}{4}:\dfrac{1}{18}=\dfrac{54}{4}=\dfrac{27}{2}\)
c: \(\Leftrightarrow\left(-\dfrac{6}{5}+x\right):\left(-3.6\right)=-\dfrac{7}{4}+\dfrac{1}{4}\cdot8=\dfrac{1}{4}\)
=>x-6/5=-9/10
=>x=3/10
`1/3 - 4/9 xx x =3/5`
`=> 4/9 xx x =1/3-3/5`
`=> 4/9 xx x = 5/15 -9/15`
`=> 4/9 xx x = -4/15`
`=>x= -4/15 : 4/9`
`=>x=-4/15 xx 9/4`
`=>x=-3/5`